Giulio Carlo Argan esordiente e l’architettura contemporanea. Da Sant’Elia a Gropius e Wright via Persico e Pagano, da Torino a Roma, da Lionello Venturi a Giuseppe Bottai - Perini Folesani, Giovanna (Lo sguardo rinnovato, 2026)
Rereading Argan’s youthful essays on architecture (namely modern architetcture) written in 1930-1941 in context, as evidence of his “militancy in the field of modern art” stemming from his academic “militancy with Venturi” implies acknowledging his start in the wake of his mentor’s politics and aesthetics, which in turn explains his original lack of sympathy for various strains of modern architecture (futurism, modernism/rationalism). Subsequently he comes to a sharp distinction of such strains, thanks to his attendance of the “Casabella” editorial board. His activity as a museum officer, involved in exhibition projects or in their assessment (when he had to supervise his colleagues’ work as a central inspector at the Ministry of Education) would lead him to the functional appreciation of modernism when severed from its fascist interpretation, This would help him reach his own final evaluation of modern architecture, design and town planning, which was to be handy during his short, intense and incisive term of office as the Lord Mayor of Rome (1976-1979).